Effects of Different Essential Oils on the Acceptability and Palatability of Cereal-Based Baits for Laboratory Mice - Jokić, Goran I; Vukša, Marina M; Đedović, Suzana; Stojnić, Bojan; Kataranovski, Dragan S; Šćepović, Tanja (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The aim of our study was to investigate the possibility of application of essential oils as additives in cereal-based rodenticide baits, at rates which prevent mould development and are applicable in humane medicine. Also, the purpose of these oils would be to extend the utility value of baits and reduce the use of antifungal ingredients that usually affect bait acceptance. The effects of essential oils of ten different plant species, applied at rates of one and two ml per kg of plain bait, on bait acceptance and palatability in choice feeding tests for Swiss mice were studied under controlled laboratory conditions. Baits were prepared according to relevant EPPO standards (2004). The effects of essential oils on bait acceptance and palatability for Swiss mice were determined in choice feeding tests using a formula by Johnson and Prescott (1994). There was no significant statistical difference in effects between groups and sexes regarding weight change in the experiment. During the experiment and recovery period, neither change in mice behavior no deaths were observed. Cinnamon and anise essential oils, commonly used as attractants, and clove oil, were most effective because they had no negative effect on bait acceptance and palatability, while fenchel and bergamot oils showed repellent activity that grew as the oil content in baits increased.
Keywords: Rodenticide baits; Essential oils